IMPLEMENTING TASK-BASED LANGUAGE TEACHING IN SPEAKING CLASS TO HOSPITALITY STUDENTS AT ALPHA UNIVERSITY PONTIANAK - Aflah, Mita Nur; Salam, Urai; Sada, Clarry (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: This study was to find out the extent to which task-based language teaching is applicable and influenced classroom practices and students? performance. The study recorded the implementation of task-based language teaching in order to find the improvement in the teaching learning process, including students? improvement in speaking skills. The data were gathered from classroom observations and interview. The analysis showed how TBLT framework gave an improvement in teaching learning process. It provided exposures, opportunities to use the language, and prudence feedback as well as motivation to help the teacher managing classroom interaction and maximizing opportunities for students to put their limited language to genuine use. It also enabled the students to experience the language; they made noticeable progress in their language learning, gaining the confidence to express themselves more fluently in speaking. In short, this study showed that has TBLT promoted students active participation in the activities with more opportunities to display their thinking through action which in turn increased their positive attitude for language learning. Key words: Task-Based Language Teaching, exposure, speaking.    Abstrak: Tujuan dari penelitian ini untuk mengetahui sejauh mana pengajaran bahasa berbasis tugas dapat mempengaruhi proses belajar mengajar dan kinerja siswa. Data diperoleh dari observasi kelas dan wawancara. Hasil analisis menunjukkan bahwa penerapan TBLT memberikan perbaikan dalam proses belajar mengajar. Adanya eksposur, kesempatan untuk menggunakan bahasa, dan umpan balik serta motivasi dapat membantu guru mengelola interaksi kelas dan memaksimalkan kesempatan bagi siswa untuk bereksperimen dengan bahasa. Hal ini juga memungkinkan siswa untuk lebih percaya diri sehingga dapat mengekspresikan diri lebih lancar dalam berbicara. Singkatnya, penelitian ini menunjukkan bahwa pengajaran bahasa berbasis tugas dapat menumbuhkan partisipasi aktif siswa dalam kegiatan dengan belajar dan meningkatkan sikap positif mereka untuk belajar bahasa. Kata kunci: Pengajaran Berbasis Tugas, Eksposur, Berbicara.